Gaya Manajemen Konflik Kompromi Pada Konflik Antar Teman Di Sma Negeri Rambipuji Jember - A, Audy Dian Febbian; A, , Rasyidah Primadita; Navillah, Nuriyatun; F, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2022)
Conflict management which is a way or strategy of individuals who behave with other people in a conflict. An individual's way of determining attitudes and behavior in dealing with interpersonal conflict so that the conflict that occurs has a positive impact. A conflict can occur between friends, whether it's in the school, home, or community environment. The purpose of this research is to find out whether there is a conflict management style between friends in resolving a conflict. This research uses a qualitative descriptive research method. Qualitative descriptive research is a research technique that produces descriptive data in the form of spoken words and the behavior of a person being observed. In this study, data analysis was obtained through a qualitative descriptive method which was carried out by analyzing the data model of Miles and Huberman.